Electrical Parameters Associated With Discharges in Resistive Soils - Espel, Patrick (2004)
The electrical parameters associated with discharges in resistive soils have been studied under inhomogeneous fields in order to achieve a better understanding of the nonlinear behavior of  rounding systems subject to high surge currents. The soil resistivity and the other parameters associated with discharges are defined using experimental and calculating methods. The dielectric strength is found to be a function of water content of the soil. The same goes for the discharge-guiding field. The inception current has been also measured and the experimental results are in good agreement with the calculated values.